Modelling of Nonuniform RC Structures for Computer Aided Design - Muhammad Taher Abuelma'atti (Active and Passive Electronic Components)
A simple model for nonuniform distributed RC structures is presented. The model consists of three passive elements only and can be used for modelling nonuniform distributed RC structures involving exponential, hyperbolic sine squared, hyperbolic cosine squared and square taper geometries. The model can be easily implemented for computer-aided analysis and design of circuits and systems comprising nonuniform distributed RC structures.